(untitled) (International Seven Journal of Multidisciplinary, 2024)
The increasing theoretical concern with possible complementarities between the social protection and the capitalist production systems is addressed in this paper. The theoretical background is based on the Welfare (RB) and Varieties of Capitalism (VoC) approaches. The integrating these two approaches is due to the assumption that Brazil shelters a variety of combinations of these systems and cannot be typified as a homogeneous type. The territorial scale adopted for the research was the Federative Units. The main aim of this study was to characterize the welfare regimes and the varieties of capitalism in the Brazilian States and test the determination between them. To achieve this aim, unlike previous studies, an ethnic dimension was included in the composition of the State types found, a theme which seems to be neglected in the specialized literature. The use of factorial, cluster and panel data analyses led to the conclusion that the social protection regimes in the Brazilian federative units are determined by the different economic production regimes.